Activating Three Languages Simultaneously in Mental Lexicon: An Investigation of Nepali – English – Sanskritparallel Language Activation - Pathak, Lekhnath Sharma (Tribhuvan University Journal, 2022)
This is the first study investigating the nature of trilingual parallel language activation in Nepal-English-Sanskrit triad. Twenty-four participants have been divided into groups of 8 based on the dominance of the three language use to understand the nature of activation in three groups. Stimuli consisted of audio-visual bimodal in nature. An emerging novel technology Mouse Tracker that can study continuous unfolding of cognitive processing has been used to design the experiment and collect the software generated data. The data has been analyzed using SPSS and visualized using R. Results which showed when three languages are activated simultaneously, the phonological similarity plays a facilitating role. The results are explained in line with BLINCS (Bilingual Language Interaction Network for Comprehension of Speech) model.